Macrophage migration inhibitory factor in acute kidneyinjury - Du, Yiwei; Hao, Hao; Ma, Heng; Liu, Hongbao (Frontiers in Physiology, 2022)
Acute kidney injury (AKI) is a complex clinical syndrome with multiple etiologies and pathogenesis, which lacks early biomarkers and targeted therapy. Recently, macrophage migration inhibitory factor (MIF) family protein have received increasing attention owing to its pleiotropic protein molecule character in acute kidney injury, where it performed a dual role in the pathological process. macrophage migration inhibitory factor and macrophage migration inhibitory factor-2 are released into the peripheral circulation when Acute kidney injury occurs and interact with various cellular pathways. On the one hand, macrophage migration inhibitory factor exerts a protective effect in anti-oxidation and macrophage migration inhibitory factor-2 promotes cell proliferation and ameliorates renal fibrosis. On the other hand, macrophage migration inhibitory factor aggravates renal injury as an upstream inflammation factor. Herein, we provide an overview on the biological role and possible mechanisms of macrophage migration inhibitory factor and macrophage migration inhibitory factor-2 in the process of Acute kidney injury and the clinical application prospects of macrophage migration inhibitory factor family proteins as a potential therapeutic target.